Creative personality: Unveiling the school impacts on student well-being - Aziz, Rahmat (Universitas Jambi, Indonesia, 2025)
This study investigates the factors influencing student well-being in middle and high schools, focusing on school climate, classroom, and creativity. Utilizing a quantitative research design, data were collected from 600 students using three validated scales: the multidimensional school climate questionnaire, the creativity scale, and the well-being scale. Descriptive and regression analyses reveal a positive school climate and innovative classroom practices significantly enhance student creativity and well-being. Furthermore, creativity mediates the relationship between schools’ role and student well-being, indicating that the positive effects of a supportive school environment on well-being are primarily due to increased creativity. These findings underscore the importance of fostering a supportive and engaging educational environment to promote students' creativity and well-being. The study's results offer valuable insights for educators and policymakers in developing targeted interventions to enhance student creativity and well-being.